Back to (the Future) School. Reshaping the Relationship Between Mobility and Schools - Fabrizia Cannella; Samuel Fattorelli; Maria Chiara Tosi; Valentina Rossella Zucca (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The paper proposes the first results of the La mia scuola va in classe A project, a participatory research and planning process promoted by the City of Venice, with the collaboration of the Cooperativa Sestante di Venezia and the Iuav University of Venice. Co-funded by MIT’s “National Experimental Program of Sustainable Home-School and Home-Work Mobility.” The project tries to rethink the relationship between school and city, between school spaces and urban fabric, through the development of educational and participatory processes aimed at the school system. The participatory pathway involves the school community in developing actions and interventions that promote active mobility on home-school routes and a rethinking of the street, threshold and proximity spaces of four inland Venetian elementary schools. Through a reconstruction of the process, we reflect on how to interweave relationships and mutual learning between school and city, with the shared elaboration of an imaginary oriented toward active mobility, awareness of the importance of motor autonomy and the psycho-physical well-being of the local community. The proposed design solutions will have the role of holding together the different instances in a fertile path leading to the improvement of the conditions of the spaces of mobility and proximity, with the idea of opening the city to the school and the school to the city, to improve the relationship between people and to return spaces of possibility to children.